Genetic structure of Solidago × niederederi (Asteraceae) population in the «Aleksin Bor» Natural Monument (European Russia) - Lysenkov, Sergey N.; Galkina, Maria A. (Nature Conservation Research: Заповедная наука, 2023)
Solidago × niederederi (Asteraceae) is a natural hybrid of the native S. virgaurea and the alien invasive S. canadensis, originated in Europe. Its naturalisation potential is still questionable. One of the largest (more than 20 ramet clusters, treated as individuals) known population of this nothospecies, is located in the «Aleksin Bor» Natural Monument (Aleksin town, Tula Region, Russia) in the floodplain of the River Oka. We studied its genetic structure with the help of chloroplast and nuclear markers. Analysis of sequence of nuclear ribosomal internal transcribed spacer ITS 1–2 showed that all individuals with intermediate morphology are actually hybrids. Data on the intergenic chloroplast non-coding spacer rpl32–trnL showed that S. canadensis is the maternal species in 60% of the studied individuals. It was shown that even closely located individuals were not clones; therefore, they were results of sexual, rather than vegetative reproduction. Analysis of ISSR markers showed that the studied individuals of S. × niederederi in this population are not only F1 hybrids, but also their descendants (F2 hybrids and/or backcrosses, mostly with S. canadensis). We conclude that S. × niederederi has successfully been naturalised in the studied community and, possibly, is outcompeting its native parental species, S. virgaurea, through introgression.